Antioxidant And Alpha Glucosidase Inhibitory Activities Of Extracts From Cucurbit Fruits And Identification Of Active And Major Constituents From Phenolic-Rich Extracts Of Lagenaria Siceraria And Sechium Edule - Supriatno, Supriatno (2013)
Eighteen fruit samples from Cucurbitaceae family that are commonly found in Malaysia, were selected in this study. All extracts were evaluated for their antioxidant activities and total phenolic contents. The primary antioxidant activities were evaluated using 1, 1 diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging and reducing power assays, and the secondary antioxidant activity was determined using metal chelating assay. For fruits that are edible in raw form, they were freshly extracted, whereas for the cooking vegetables, they were being boiled prior to extraction. Different percentages of ethanol in distilled water (0, 20, 40, 60, 80 and 100%) were used as the extraction solvents and 80% (v/v) ethanol extract of Lagenaria siceraria showed the highest DPPH, reducing power and metal chelating activities with the EC50 values of 8.85 ± 0.09 mg/mL, 28.33 ± 1.67 mg/mL, and 6.51 ± 0.17 mg/mL, respectively. Furthermore, four solvents of ascending polarities (hexane, chloroform, ethyl acetate and methanol) were being used to sequentially extract the dried fruit samples. The methanol and ethyl acetate extracts of L. siceraria respectively showed the highest DPPH (EC50 = 370.01 ± 12.51 and 469.00 ± 2.89 μg/mL) and metal chelating activities (EC50 = 249.78 ± 5.03 and 203.44 ± 4.01 μg/mL), while the ethyl acetate extract of Sechium edule showed the highest reducing power (EC50 = 409.35 ± 9.25 μg/mL).